A Gendered Approach to Forced Migration Governance in the Asia Pacific - Amalia, Annisa Dina (UI Scholars Hub, 2018)
Despite persecution of refugees being in the spotlight around the world, academics and practitioners continue to debate how to address the issue. Using a feminist lens in International Relations, this paper attempts to unpack the seemingly neutral character of forced migration governance. Supported by examples from the Asia Pacific region, this paper finds that the nature offorced migration governance is highly gendered. This can be seen from how states portray andtake actions towards refugees within ASEAN and the Bali Process, as these are the two maininstitutions governing forced migration in the region. This governance is gendered through: (1) the feminization of refugee portrayal by states’ security-focused approach, and (2) the reinforcement of states’ perceptions as the masculinist protectors translated into the securitization of migration. While this understanding seems to add more complexity to the issue, it further suggests that this state- and security-centric paradigm can be reconstructed by a rapprochement between feminist and International Relations scholars.